Mitochondrial rate variation among lineages of passerine birds. (4th April 2016) - Nguyen, Jacqueline M. T.; Ho, Simon Y. W.
Abstract : The order Passeriformes comprises the majority of extant avian species. Analyses of molecular data have provided important insights into the evolution of this diverse order. However, molecular estimates of the evolutionary and demographic timescales of passerine species have been hindered by a lack of reliable calibrations. This has led to a reliance on the application of standard substitution rates to mitochondrial DNA data, particularly rates estimated from analyses of the gene encoding cytochrome b ( CYTB ). To investigate patterns of rate variation across passerine lineages, we used a Bayesian phylogenetic approach to analyse the protein‐coding genes of 183 mitochondrial genomes. We found that the most commonly used mitochondrial marker, CYTB, has low variation in rates across passerine lineages. This lends support to its widespread use as a molecular clock in birds. However, we also found that the patterns of among‐lineage rate variation in CYTB are only weakly related to the evolutionary rate of the mitochondrial genome as a whole. Our analyses confirmed the presence of mutational saturation at third codon positions across the protein‐coding genes of the mitochondrial genome, reinforcing the view that these sites should be excluded in studies of deep passerine relationships. The results of our analyses have provided information that will be useful for molecular‐clock studies of passerine evolution.